Enhancing motivation and psychological wellbeing in the workplace through conscious physical activity: Suggestions from a qualitative study examining workers' experience - Signorini, Gabriele; Scurati, Raffaele; D'Angelo, Chiara; Rigon, Marta; Invernizzi, Pietro Luigi (Frontiers in Psychology, 2022)
Introduction After COVID-19 restrictions, hybrid solutions were established that combined smart working and work in presence. Workplace conditions significantly impact employees' lives, particularly in terms of meeting their needs and promoting their wellbeing. Based on a socio-ecological and multilevel methodology, the UP150 concept (Proactive Office 150) represents a possible innovative solution to meet employees' needs and valorize flexible work. It encourages physical exercise and active breaks during the typical workday by using particular architectural modifications, a dedicated App, and physical activity professionals as wellness coaches. The present study is the last step of the preliminary actions planned to check the benefits of the UP150 concept and aims to explore the workers' perceptions after experiencing this project. Methods The qualitative analysis of a preliminary survey (concerning information about the company structure and workers' habits) performed before conducting a randomized controlled trial intervention study and the analysis of the semi-structured interviews after 8 weeks of a UP150 experience served as datasets for this study and have been examined and discussed. Results In the preliminary survey, the young (under 40) and generally active (57% of the workers) reported being motivated to exercise but inhibited by a lack of time and a heavy workload. After 8 weeks at a modified workplace designed in accordance with the motive behind the UP150, the workers displayed noticeable positive perceptions and appreciation. Discussion The qualitative analysis confirmed and supported the effectiveness of the UP150 concept that previous research had already found in quantitative parameters related to employees' motor efficiency, psychophysical status, and amount of physical activity. Participants reported beneficial perceived effects on their wellness and psychophysical status following a UP150 experience. Moreover, the concept improved social relationships and increased motivation. In conclusion, the UP150 concept efficiently fostered a positive perception of physical exercise and directed the employees toward the assumption of healthy behaviors fitting the physical literacy paradigm.